2008
DOI: 10.1246/bcsj.81.1212
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Kinetics of Cyanide Decomposition by Ferrate

Abstract: The mechanism of cyanide oxidation by ferrate in water is discussed using DFT computations in the framework of the polarizable continuum model. The reactivity of three oxidants, nonprotonated, monoprotonated, and diprotonated ferrates is evaluated. This reaction is initiated by a direct attack of an oxo group of ferrate to the carbon atom of cyanide, followed by an H-atom transfer from cyanide to another oxo group to lead to an intermediate having cyanate (NCO À ) as a ligand. The produced cyanate is oxidized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Typical examples with inorganic reductants are the oxidation of iodide to iodine, arsenite to arsenate, or of sulfite/selenite to sulfate/selenate,, , , but also of hydrogen peroxide, alkali superoxides, hydrazines, hydroxylamines, azide, nitrite, hydrogen sulfide, cyanide,, thiocyanate, hexacyanoferrate(II), thiosulfate,, dithionite, chromium(III), and many others.…”
Section: The Chemistry Of Ferrates(vi)mentioning
confidence: 99%
“…Typical examples with inorganic reductants are the oxidation of iodide to iodine, arsenite to arsenate, or of sulfite/selenite to sulfate/selenate,, , , but also of hydrogen peroxide, alkali superoxides, hydrazines, hydroxylamines, azide, nitrite, hydrogen sulfide, cyanide,, thiocyanate, hexacyanoferrate(II), thiosulfate,, dithionite, chromium(III), and many others.…”
Section: The Chemistry Of Ferrates(vi)mentioning
confidence: 99%
“…6 and 7). According to density functional theory (DFT), HFeO 4 À has a larger spin density on the oxoligands than does FeO 4 2À , which increases the oxidation ability of HFeO 4 À species (Kamachi et al, 2005(Kamachi et al, , 2008. This has been demonstrated by performing calculations on the reactivity of ferrate(VI) with several compounds (Kamachi et al, 2005(Kamachi et al, , 2008Ohta et al, 2001;Shiota et al, 2003).…”
Section: Ph Effectmentioning
confidence: 99%
“…This is because HFeO À 4 reacts with compounds more rapidly than FeO 2À 4 does. Density functional theory calculations on the reactivity of ferrate(VI) with compounds have shown that protonated ferrate(VI) has a larger spin density on the organic compounds than unprotonated ferrate(VI), which increases the oxidation ability of protonated ferrate(VI) [40]. Furthermore, ferrate(VI) yields Fe(II) and Fe(III) as reduced products, and different numbers of oxygen atoms are being transferred to form oxidized products.…”
Section: Zps and Psdmentioning
confidence: 99%